Céline Martin’s Images of Thérèse of Lisieux and the Creation of a Modern Saint - Deboick, Sophia L. (Studies in church history, 2011)
At the time of the death of Sœur Thérèse de l’Enfant-Jésus (Marie-Françoise-Thérèse Martin, 2 January 1873 — 30 September 1897) the Carmelite convent of Lisieux was a hidden and poor community, destined to remain as obscure and forgotten as Thérèse herself had been during her nine-year career as a nun. Just twenty-eight years later, Thérèse had been made a saint and the Carmel of Lisieux had become the focus of the attention of the whole Catholic world. There was little remarkable about Thérèse’s short and sheltered life, but she has enjoyed an incredible ‘posthumous life’ through her second career as a saint. The autobiographical writings she produced during her time at the Carmel were published in 1898 as L’Histoire d’une âme (The Story of a Sout) and were an instant success, later becoming a classic of Catholic spirituality. Her canonization in 1925 was the quickest since 1588 at the time, and Pope Pius XI referred to her rapid rise to fame as a ‘storm of glory’, later calling her ‘the star of his pontificate’. Named Patroness of the Missions in 1927, she became Patroness of France, alongside Joan of Arc, immediately after the liberation of France in 1944, and in 1997 Pope John Paul II named her a Doctor of the Church. Only the third woman to earn this title, she became ranked alongside the legendary names of Teresa of Àvila and Catherine of Siena. Since 1994 her relics have been on an almost constant world tour and when they visited Ireland in 2001 the organizers estimated that seventy-five per cent of the total population turned out to venerate them — some 2.9 million people. In September and October 2009 they visited England and Wales, a unique event in the religious history of Britain, which stimulated considerable interest in Thérèse as a historical personality. But while the biographies of Thérèse proliferate, the importance of her posthumous existence for European religious culture continues to be overlooked. This paper looks at the construction of the cult of Thérèse of Lisieux after her death, paying particular attention to the role which the Carmel of Lisieux and its key personalities played in this process, and highlighting the central role played by images and commercial products in the development of the cult.